Application of Mud Suction Technology to Lakes in Kaduela Village, Pasawahan District, Kuningan Regency - Nurdiyanto; Akbar Winasis; Ramlah Puji Astuti; Rendy Yogista Wihardi; Ghisya Siti Rochmah (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2024)
A decrease in water potential, both in quality and quantity, will become a problem if it is not managed properly by paying attention to aspects of conservation, utilization, and control. This community empowerment carried out from July to November 2023 is an effort to increase awareness of water resources through preserving water sources to meet the needs of living creatures. The urgency of the main problem is that the water source in Telaga Biru Cicerem, Kaduela Village, Pasawahan District, Kuningan Regency, has been naturally covered with mud, whereas this spring is used as clean water for the village community. The second problem is that clean water sources become cloudy because of mud. The clean water system in this village relies solely on the lake's spring water. These activities of community empowerment are carried out by applying the method of SEPUR (Mud Suction) Technology to improve water quality as well as increase the income of village-owned enterprises in Kaduela Village, Pasawahan District, Kuningan Regency. The results show that mud can be lifted by machines so that the lake water becomes clear, while the resulting mud residue can be used as material for making paving blocks.